The Urgence of Disaster Applications in The Era of Community 5.0 - Imran Kahar (Iapa Proceedings Conference, 2021)
People have been familiar with applications since the introduction of computers as a tool in completing work, whether in offices, companies and other businesses, where applications are now not a rare item because almost all people have smartphones. The Inarisk Disaster Application and BMKG Info that have been issued by BNPB and BMKG is an application that can be accessed by the general public to find out the possible places where disasters will occur around us, both natural and non-natural disasters. Indonesia is one of the countries that is very prone to disasters where Indonesia has several tectonic plates and is also traversed by the ring of fire zone which is very susceptible to various kinds of disasters so that a breakthrough is needed in making applications that can be connected and accessible to the public, not only those who have smartphones. live in urban areas but people live in remote areas. The government's efforts in realizing a more comprehensive disaster application need to be realized immediately because society is currently moving towards society 5.0. where all work and activities are supported by application-based technology, in addition to the existence of disaster applications, it means that the community and government can carry out early detection and prevention of possible disasters that will occur.